1970
DOI: 10.3126/narj.v6i0.3368
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Improved Feeders for Goats Suitable to Stall-fed Management System

Abstract: Five different types of feeders were designed and tested on goats to find out their effectiveness in reducing feed wastage and cost fabrication. Experiment was conducted at Agriculture Research Station (ARS)-Bandipur for two years. Tested feeders were hexagonal, rectangular, hay rack, chain barrel and conventional wooden Tatnu. Feeders were fabricated using iron bars and woods. They were tested with the adult goats for feed wastage and feed contamination. Experimental feeds were fodders twigs (Tanki), forage (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…This compensates for the fact that the animals at the feeding barrier cannot feed as they would on pasture (i.e., they cannot splay their legs, a posture which allows them to reach the ground easily with their muzzle). Consequently, some authors also suggest such a height difference for goats (Peacock, 1996;Muhikambele et al, 1998;Upreti et al, 2005). Our data demonstrate that the minimum height difference between standing surface of forelegs and feed table should not be less than 10 cm.…”
Section: Discussionsupporting
confidence: 56%
“…This compensates for the fact that the animals at the feeding barrier cannot feed as they would on pasture (i.e., they cannot splay their legs, a posture which allows them to reach the ground easily with their muzzle). Consequently, some authors also suggest such a height difference for goats (Peacock, 1996;Muhikambele et al, 1998;Upreti et al, 2005). Our data demonstrate that the minimum height difference between standing surface of forelegs and feed table should not be less than 10 cm.…”
Section: Discussionsupporting
confidence: 56%
“…Bedding substrates vary between regions, but straw (United Kingdom, Anzuino et al, 2010 ; Italy, Battini et al, 2016 ) and wood shavings (Norwegian producer-reported survey, Simensen et al, 2010 ) are common. Most housing systems provide feed at ground level along the outside of a feed rail that is accessible by machinery along a drive alley, but depending on the feed, elevated racks, troughs, and conveyor belts are also used (e.g., Upreti et al, 2005 ). The design of the feed rail can vary widely as it is dependent on whether the goats are horned ( Loretz et al, 2004 ; Nordmann et al, 2015 ).…”
Section: Commercial Dairy Goat Housingmentioning
confidence: 99%
“…After regrouping, a comparative increase in feed intake in does was noticed in both types of feeder which might be due to more competitiveness among new group mates, contrarily overall feeding activities (positive as well as negative) were decreased at both type of feeders (Kaur 2019). Upreti et al (2005) noted that green forage wastage for stylo and napier were significantly lower in rectangular (7.74, 13.86%) followed by chain barrel (17.3, 19.5%), hexagonal (20.49, 27.49%) and hay rack (29.61, 16.66%). Wastage of straw (black bean) and fodder twigs (tanki) too had similar trend.…”
Section: Resultsmentioning
confidence: 96%
“…Wastage of straw (black bean) and fodder twigs (tanki) too had similar trend. Findings of Upreti et al (2005) clearly indicates that wastage at rectangular and chain barrel feeders (both had linear dimensions) were lesser than hexagonal and circular feeders (round dimensions). Kumari and Patel (2015) concluded that linear feeding trough helped in saving the green fodder (wastage) in comparison to circular (hexagonal) feeder and provision of unchopped fodder in circular feeder did not give any advantage over linear feeding trough.…”
Section: Resultsmentioning
confidence: 97%